Հայ ձեռագրարվեստի ուսումնասիրությունը թվային դարում - Սարգսյան, Լուսինե (Մատենադարան)
The study of manuscripts through digital technologies occupies a significant place among the strategic projects of the Matenadaran after Mesrop Mashtots in recent years. In this regard the Digitization department of Matenadaran, is doing an important work by digitizing the manuscripts kept in the Matenadaran. Copies of some of these digitized manuscripts were once available on the website of Matenadaran (www.matenadaran.am, The Lectionary of the King Hetum the Second, Ms 979, the Gospel of Eight painters, Ms 7651, and etc.). The Department for the Study of the History of Art and Scriptoria at Matenadaran has initiated projects that will greatly promote the study of Armenian manuscript art in the field of Digital Humanities. One of them – the “Armenian Manuscript Illumination” project (hereinafter referred to as AMI) is currently being implemented. The goal of the AMI project is to make the Armenian manuscript art accessible to a wider audience, using tools provided by digital science. It is one-of-a-kind project (website: www.armenoids. com) featuring a complete system of illumination of Armenian manuscripts through a comparative table. The website is designed in two languages: Armenian and English.
Keywords: Հայ արվեստ; Ձեռագրարվեստ